Readiness construction employee towards occupational safety and health programme - Azmi, Hassan; Noor Aina Amirah, Mohd Noor; Nik Fadhilah, Nik Him (2019)
The aim of this study is to identify the construction practitioners’ level of readiness toward occupational safety and health program. The level of employee readiness is assessed through a survey method involving construction site workers. This study involved the distribution of questionnaires to the whole population as main instrument in data obtaining. Hence, the data obtained were analysed descriptively using frequency, percentage and mean score to identify the level of readiness of respondents to safety and health at the workplace. Crosstab analysis is used to examine the relationship between demographic factors and the level of respondents’ readiness toward occupational safety and health. The level of readiness among 125 construction workers toward occupational safety and health programs was high with a mean average score of 3.82. The results of the Crosstab analysis showed that there was a significant relationship between demographic factors and readiness toward occupational safety and health that led to accidents at construction sites. In order to increase the level of readiness of respondents of site workers, the organization should held more safety and health programs such as trainings, talks on importance of safety and health, or overall enforcement.